Informal waste collectors and aggregators space and activities in Buon Ma Thuot city, Vietnam, COMPOSE project (2019-2021) - Nguyen, Thai Huyen; Ngo, Minh Vu; Le, Thi Thao Trang; Nguyen, Thai Hoa; Nguyen, Thi Hai Yen; Dinh, Ngoc Anh; Le, Viet Anh; Le, Tuan Minh; Phan, Cong Hung; Nguyen, Tien Tam; Nguyen, Thi Mo; Trinh, Dai Cuong; et al. (DataSuds, 2021)
The system of informal waste collectors and aggregators in Buon Ma Thuot city (Vietnam) was surveyed in the framework of the COMPOSE project (2019-2021). The social survey based on questionnaire was carried out in the entire area of in Buon Ma Thuot city, Dak Lak province, to identify the location of the aggregator warehouse participating to the informal waste collection and recycling in the city. Then, the collectors and aggregators were interviewed individually to collect information on the space, architectural characteristic of the warehouse, the neighborhood, the hours of operation, the type of materials collected and on the owners of the warehouse (hometown, the reasons for choosing the job). The quantitative surveys were conducted in November 2019 and in October 2020. Data anonymization was performed by removing identifiers, generalization (grouping precise values into less precise/larger categories) and finally by aggregating individual records, producing descriptive statistics (frequencies).